Scots Pine Needles As Bioindicators In Determining The Aerial Distribution Pattern Of Sulphur Emissions Around Industrial Plants - Pöykiö, Risto; Hietala, Jari; Nurmesniemi, Hannu (Zenodo, 2010)
In this study, the Scots pine (Pinus sylvestris L.) C needles (i.e. the current-year-needles) were used as bioindicators in determining the aerial distribution pattern of sulphur emissions around industrial point sources at Kemi, Northern Finland. The average sulphur concentration in the C needles was 897 mg/kg (d.w.), with a standard deviation of 118 mg/kg (d.w.) and range 740 – 1350 mg/kg (d.w.). According to results in this study, Scots pine needles (Pinus sylvestris L.) appear to be an ideal bioindicators for identifying atmospheric sulphur pollution derived from industrial plants and can complement the information provided by plant mapping studies around industrial plants. : {"references": ["J. Poikolainen, \"Mosses, epiphytic lichens and tree bark as biomonitors\nfor air pollutants - specifically for heavy metals in regional surveys,\"\nDoctoral Thesis. Acta Universitatis Ouluensis, A 421. Oulu University\nPress, Oulu, Finland, 2004.", "K. Ots, and V. Reisner, \"Scots pine (Pinus sylvestris L.) and its habitat in\nMuraka bog under the influence of wastes from the Narva power plants\n(North-East Estonia),\" Proc. Estonian Acad. Sci. Biol. Ecol., vol. 55, pp.\n137-148, 2006.", "P. Rautio, and S. Huttunen, \"Total vs. internal element concentrations in\nScots pine needles along a sulphur and metal pollution,\" Environ.\nPollut., vol. 122, pp. 273-289, 2003.", "A. Laamanen, and R. Lahdes, \"Observations on sulphur content of pine\nneedles from the environment of point and area sources,\" Work Environ.\nHealth, vol. 6, pp. 41-43, 1969.", "R. P\u00f6yki\u00f6, H. Nurmesniemi, V.A. Kivilinna, and J. Hietala, \"Long-term\nchanges in sulphur concentrations in Scots pine (Pinus sylvestris L.)\nneedles in the area around pulp and paper mills at Kemi, Northern\nFinland,\" J. Int. Environmental Application & Science, vol. 5, pp. 9-16,\n2010.", "R. P\u00f6yki\u00f6, V.A. Kivilinna, and H. Nurmesniemi, \"Pine needles (Pinus\nsylvestris L.) as a bioindicator of sodium and calcium deposition in the\narea around pulp and paper mills at Kemi, Northern Finland,\" Chemija,\nvol. 21, pp. 42-47, 2010.", "R. P\u00f6yki\u00f6, and H. Torvela, \"Pine needles (Pinus sylvestris L.) as a\nbioindicator of sulphur and heavy metal deposition in the area around a\npulp and paper mill complex at Kemi, Northern Finland.\" Inter. J.\nEnviron. Anal. Chem., vol. 79, pp. 143-154, 2001.", "A. Tammilehto, S. Hamari, \"M\u251c\u00f1nnynneulasten rikkipitoisuus- ja\nvaurioselvitys Kemiss\u251c\u00f1 ja Keminmaassa vuonna 2009\", Lapin\nVesitutkimus Oy, 2009 (in Finnish).", "R. C. Eagan, P. V. Hobbs, and L. F. Radke, \"Particle emissions from a\nlarge kraft paper mill and their effects on the microstructure of warm\nclouds\", J. Appl. Meteorol., vol. 13, pp. 535-552, 1974.\n[10] J. C.M. Bordado, and J. F.P. Gomes, \"Atmospheric emissions of kraft\npulp mills\", Chem. Eng. Proc., vol. 41, pp. 667-671, 2002.\n[11] A. Tohka, and N. Karvosenoja, \"Final particle emissions and emission\nreduction potential in Finnish industrial processes\", Report of Finnish\nInstitute 21/2006. Edita Prima Ltd., Helsinki, 2006.\n[12] A. J. Lindroos, J. Derome, K. Derome, and M. Lindgren, \"Trends in\nsulphate deposition on the forest and forest floor and defoliation degree\nin 16 intensively studied forest stands in Finland during 1996-2003,\"\nBoreal Env. Res., vol. 11, pp. 451-461, 2006.\n[13] R. P\u00f6yki\u00f6, H. Nurmesniemi, J. Hietala, P. Parvinen, P. Per\u251c\u00f1m\u251c\u00f1ki, and K.\nWieczorek-Ciurowa, \"Scots pine (Pinus sylvestris L.) needles as\nbioindicators in determining the distribution pattern of aerial sulphur\nemissions from industrial plants at Kemi, Northern Finland,\" 15th\nInternational Conference on Heavy Metals in the Environment. 19 -\n23th September 2010, Gdansk, Poland, Proceedings, pp. 972-974, 2010.\n[14] J. L. Innes, \"Influence of air pollution on the foliar nutrition of conifers\nin Great Britain\", Environ. Pollut., vol. 88, pp. 183-192, 1995.\n[15] P. Rautio, S. Huttunen, and J. Lamppu, \"Seasonal foliar chemistry of\nNorthern Scots pines under sulphur and heavy metal pollution,\"\nChemosphere, vol. 37, pp. 271-287, 1998."]}